Pharmacokinetics, biological effects, and distribution of (1→3)-β-D-glucan in blood and organs in rabbits - Minoru Yoshida; Robert I. Roth; Carl Grunfeld; Kenneth R. Feingold; Jack Levin (Mediators of Inflammation)
The pharmacokinetics, biological effects and distribution in blood and organs of 125I-labeled (1→3)-β-D-glucan purified from Candida albicans were analyzed in rabbits during the 24-h period following an intravenous administration.The intravascular half-life of (1→3)-β- D-glucan was 1.8 min in the low-dose group (9.3 μg/kg) and 1.4 min in the high-dose group (222 μg/kg), and the mean (±SD) total body clearance was 1.12 ± 0.30 and 1.17 ± 0.16 ml/min, respectively. The rabbits remained well and (1→3)-β-D-glucan failed to alter blood cell counts. Less than 3% of the 125I-(1→3)-β-D-glucan was initially associated with the cellular compartment, and this value decreased further during the 2-h period following administration (P = 0.0001). Over 97% of 125I-(1→3)-β-D-glucan was associated with cell-free plasma, and the majority in plasma appeared to be present in the unbound form (not associated with lipoproteins or plasma proteins). The liver contained more than 80% of the 125I-(1→3)-β-D-glucan detected in the six major organs analyzed.